Aortic Pulse Wave Velocity Predicts Cardiovascular Events and Mortality in Patients Undergoing Coronary Angiography: A Comparison of Invasive Measurements and Noninvasive Estimates. Issue 2 (February 2021) - Hametner, Bernhard; Wassertheurer, Siegfried; Mayer, Christopher Clemens; Danninger, Kathrin; Binder, Ronald K.; Weber, Thomas
Abstract : Aortic pulse wave velocity (PWV) is directly related to arterial stiffness. Different methods for the determination of PWV coexist. The aim of this prospective study was to evaluate the prognostic value of PWV in high-risk patients with suspected coronary artery disease undergoing invasive angiography and to compare 3 different methods for assessing PWV. In 1040 patients, invasive PWV (iPWV) was measured during catheter pullback. Additionally, PWV was estimated with a model incorporating age, central systolic blood pressure, and pulse waveform characteristics obtained from noninvasive measurements (estimated PWV). As a third method, PWV was calculated with a formula solely based on age and blood pressure (formula-based PWV). Survival analysis was based on continuous PWV as well as using cutoff values. After a median follow-up duration of 1565 days, 24% of the patients reached the combined end point (cardiovascular events or mortality). Cox proportional hazard ratios per 1 SD were 1.35 for iPWV, 1.37 for estimated PWV, and 1.28 for formula-based PWV ( P <0.0001 for all 3 methods) in univariate analysis, remaining statistically significant after comprehensive multivariable adjustments. In a model including a modified risk score for coronary artery disease, iPWV and estimated PWV remained borderline significant. The net reclassification improvement was significant for iPWV (0.173), formula-based PWV (0.181), and estimated PWV (0.230). All 3 methods for the determination of PWV predicted cardiovascular events and mortality in patients with suspected coronary artery disease. This indicates that iPWV as well as both noninvasive estimation methods are suitable for the assessment of arterial stiffness, bearing in mind their individual characteristics. Abstract : Supplemental Digital Content is available in the text.